PROFIL PENGGUNAAN STATISTIKA DALAM PENELITIAN MAHASISWA PENDIDIKAN MATEMATIKA - Eriska Fitri Kurniawati; Edy Nurfalah; Tanti Nawangsari (FKIP Unirow Tuban, 2018)
This study was conducted to describe the use of statistics by students in the Ronggolawe University (Unirow) Mathematics Education thesis. In research in various fields, statistics are widely used, especially those relating to data analysis techniques, namely to analyze and draw conclusions based on data and analysis carried out. The results showed that the students of Ronggolawe University Mathematics Education thesis used more descriptive statistics than those using inductive (inferential), parametric and non-parametric statistics. Students who used descriptive statistics were 81 students (76.42%), inferential statistics of 4 students (3.77%), parametric statistics of 16 students (15.09%), and those using 5 student non-parametric statistics (4.72 %).